Diabetic foot care : case studies in clinical management - Foster, Alethea V. M.; Edmonds, M. E.; Wiley InterScience (Online service) (Chichester : Wiley-Blackwell, 2011)
Diabetic Foot Care: Case Studies in Clinical Management uses a 100% illustrated patient case study format to demonstrate the multidisciplinary care and clinical management of patients with feet and lower limb problems as a result of diabetes. Every case has colour illustrations highlighting both the initial presentation of the foot, right through to treatment and long term follow-up care. Of particular focus are the management problems, barriers to effective care, preventable mistakes, unnecessary delays in presentations, challenging situations, conflicts, dilemmas and solutions that podiatris.
Neuropathic case studies -- Ischaemic case studies -- Charcot case studies -- Renal case studies.
Includes bibliographical references and index.
Print version record.
Keywords: Foot -- Diseases -- Treatment -- Case studies; Diabetes -- Complications -- Treatment -- Case studies; Foot manifestations of general diseases -- Case studies; Diabetic Foot -- therapy; Diabetic Foot -- diagnosis; Medicine; MEDICAL -- Nephrology; Diabetes -- Complications -- Treatment; Foot -- Diseases -- Treatment; Foot manifestations of general diseases; Electronic books; Case studies